2015
DOI: 10.1002/jcph.480
|View full text |Cite
|
Sign up to set email alerts
|

Comparing pyridoxine and doxylamine succinate‐pyridoxine HCl for nausea and vomiting of pregnancy: A matched, controlled cohort study

Abstract: Nausea and vomiting of pregnancy (NVP) is a common gestational condition. This is the first study to compare the use of vitamin B6 (pyridoxine) versus Diclectin (doxylamine succinate-pyridoxine HCl) for NVP symptoms. Participants were pregnant women with NVP who used either pyridoxine or doxylamine succinate-pyridoxine HCl for ≥4 days prior to calling the Motherisk NVP Helpline. Women receiving pyridoxine only (n = 80) were matched to a woman taking doxylamine succinate-pyridoxine HCl only (n = 80), accounting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
0
9
0
3
Order By: Relevance
“…Assessment of QOL seems important for the care of women who experience NVP [14]. The NVP‐QOL questionnaire has previously been validated and used successfully in other studies [11,12]; however, this tool includes 30 items and can take a long time to complete. Thus, it does not seem appropriate to use the NVP‐QOL score when the modified‐PUQE score is low because there will be only a slight alteration in QOL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of QOL seems important for the care of women who experience NVP [14]. The NVP‐QOL questionnaire has previously been validated and used successfully in other studies [11,12]; however, this tool includes 30 items and can take a long time to complete. Thus, it does not seem appropriate to use the NVP‐QOL score when the modified‐PUQE score is low because there will be only a slight alteration in QOL.…”
Section: Discussionmentioning
confidence: 99%
“…This score was compared with the 12‐item Short Form Health Survey and found to be effective for use during the first trimester of pregnancy [11]. Other studies have confirmed the utility of this score in the evaluation of QOL during episodes of NVP [7,12,13]. Nevertheless, few studies have been published concerning the use of these two scores among pregnant women [14].…”
Section: Introductionmentioning
confidence: 99%
“…Zu berücksichtigen sind die konträren Ergebnisse aus der kanadischen Kohortenstudie von Berard et al 2019 91 , nach der die Gabe von Doxylamin/ Pyridoxin mit einer leicht signifikanten Erhöhung des Gesamtrisikos für schwere kongenitale Anomalien assoziiert war (aOR 1,07; 95% KI 1,03–1,11), dies betraf insbesondere ein 1,8-fach erhöhtes Risiko für Spina bifida. Die alleinige Anwendung von Pyridoxin wird von der RCOG Leitlinie 2016 nicht empfohlen 95 .…”
Section: Alternative Therapienunclassified
“…Tan et al [33] pyridoxine usage in HG did not demonstrate any improvement in nausea, vomiting or rehospitalisation in 46 women given 20 mg orally three times a day in addition to intravenous fluids. Pope et al [34] demonstrated that the combination of doxylamine and pyridoxine was significantly more effective than pyridoxine alone.…”
Section: Disucssionmentioning
confidence: 99%